The 2013 Philippine Mid-term Election: An Empirical Analysis of Dynasties, Vote Buying and the Correlates of Senate Votes - Mendoza, Ronald U (Archīum Ateneo, 2019)
According to analysts, the 2013 Philippine mid-term elections provide important insights into the complexion and probable outcomes of the 2016 national elections. Key candidates forming part of the administration coalition ran for office in May (e.g. Risa Hontiveros and Bam Aquino), along with certain opposition candidates that some view act as proxies for potential presidential aspirants (e.g. Nancy Binay as a proxy for her father, incumbent Vice President Jejomar Binay). The 2013 election was also distinct because of the presence of a strong information and advocacy campaign against political dynasties. It was marked by efforts of various advocacy groups (e.g. Anti-Political Dynasty Movement, ANDAYAMO; and Movement Against Dynasties, MAD) to try and emphasize the potentially unconstitutional nature of dynasties, as well as their links to poverty and more traditional patron-client politics, seen inimical to inclusive growth and development. In addition, the election was also characterized by many reports of vote-buying. There were even claims that it had become much worse despite the computerization of elections in the Philippines since 2010 (which was partly done to mitigate election wrongdoing and anomalies, including vote-buying)…